Porta adentro : fragmentos de criação de uma primeira novela - Joanello, Caroline (2017)
The present essay consists of two parts. One, fictional, presents the novel Porta adentro, the first long narrative written by the author. Porta adentro tells the story of Cora, a young student that loses her mother in an accident and isolates herself from the rest of the apartment where they both lived in, blocking the passage for the interior of the house, until a toothache forces her to go inside and search through her mother's things for the contact of her childhood dentist, and, while looking at those documents, finds out her mother once had a different name and changed countries running away from a violent and obsessed man. Discovery that forces Cora to review her values and attitudes, as well as puts her face to face with her mother's past. The other part, theoretical, presents fragments of diaries, talks, experimental writing and a history of decisions that lead to the creation of Porta adentro, from the project to the final draft, considering this process as a path of wrongs and rights — more of those than these — characteristics of a first journey. Enlightened by creative writing and narrative theories and a little bit of genetic criticism, those fragments take the form of a self-criticism.